B- and T-cell epitope mapping of human sapovirus capsid protein: an immunomics approach. (3rd August 2011) - Amin, M. Ruhul; Siddiqui, Mohammad S.; Ahmed, Dilruba; Ahmed, Firoz; Hossain, Anowar
Human sapovirus is one of the major causes of viral gastroenteritis. Although the capsid protein (VP1) confers antigenic cross-reactivity, immunity against sapovirus is still unclear. Using immunoinformatics approach, we defined putative T- and B-cell epitopes of VP1 and mapped on to its predicted three-dimensional structure. Identified five putative T-cell epitopes also occupied the putative B-cell epitope region. These putative epitopes were conserved in all existing serotypes. Predicted epitopes can be generated through proteasome cleavage and may be useful in designing peptide-based subunit vaccine to confer both humoral and cell-mediated immunity.